Window of opportunity: examining gray wolf (Canis lupus) diets and seasonal patterns of predation on wood bison (Bison bison athabascae) ... - Dewart, Lindsey (Marine Pollution Bulletin, 2023)
Prey selection by predators is a complex process, with acquisition strategies varying between generalists and specialists. However, generalist predators like wolves (Canis lupus Linnaeus, 1758), can select prey in response to increases in abundance or vulnerability of the prey, often influenced by environmental conditions. In multi-prey systems that include bison (Bison bison Linnaeus, 1758), this is not always the case, as wolves will often select less dangerous prey. To investigate the predator-prey relationship between wolves and a small (~275 – 300 individuals) Threatened herd of wood bison (Bison bison athabascae Linnaeus, 1758) in northeast Alberta, Canada, I monitored location data from global positioning system (GPS) collars affixed to both species for one year. I evaluated seasonal differences in wolf diet, the effect of temporal variables on relative bison predation risk by wolves, and space use relative to bison for three wolf packs whose territories overlapped with the bison herd’s home range. I ...